Carbon and nitrogen stoichiometry across plant–soil system accounts for the degradation of multi-year alfalfa grassland - Wang, Wei; Tian, Tao; Li, Meng-Ying; Wang, Bao-Zhong; Mei, Fu-Jian; Li, Ji-Yuan; Wang, Ning; Yang, Yu-Miao; Zhang, Qiang; Tao, Hong-Yan; Zhu, Li; Xiong, You-Cai (Frontiers in Plant Science, 2024)
Alfalfa (Medicago sativa L.) grassland is prone to degradation following multi-year maintenance. Yet, its mechanism regarding the stoichiometry of carbon (C) and nitrogen (N) across plant-soil system is still unclear. To address this issue, the method of space-for-time sampling was employed to investigate alfalfa grasslands with five planting years (5-, 8-, 10-, 15- and 20-year periods) in the semiarid Loess Plateau. The results showed that the alfalfa above- and underground biomass decreased steadily decrease after 5-8th years, showing a degradation tendency with the extension of planting duration. The mean weight diameter of aggregate registered an increase with planting years. However, the C and N stocks decreased with planting years in five soil aggregate fractions. Specifically, they were the highest in the 5th year, and then started to gradually decrease along the 8th, 10th, 15th and 20th year. Redundancy and correlation analysis confirmed that the C and N stocks of soil aggregates were closely positively associated with those of plant. Overall, the highest stability of soil physical structure was found during the period from 5th to 8th year, and afterwards the stability declined. In conclusion, alfalfa plantation improved soil structure stability but aggravated soil C & N stocks, and biomass and soil aggregate indicators accounted for alfalfa field degradation after a certain year of plantation.